Games and the Margins: Winning Fops and Gambling Women on the Restoration Comic Stage - Clara Manco (Etudes Epistémè)
Although gambling is traditionally associated with homosocial competition and with the prestige of the aristocratic ethos, Restoration comedies abound with examples of marginal characters at the gambling table. This article explores the symbolic implications of these marginal gamblers in plays written and produced during the reigns of Charles II and James II. These characters, whether they be women or comic butts, show us to what extent gambling constitutes a moment of suspension, or even of renegociation of theatrical, social and political hierarchies, ranging from brief moments of carnivalesque relief to genuine revenge of the weak over the powerful.